Tabata Training Intervention in Combating Sedentary Lifestyle and Its Impact on VO₂ Max, Body Composition, and Lipid Profile of College Students - Yunus, Moch.; Supriyadi, Supriyadi (PT FORMOSA CENDEKIA GLOBAL, 2025)
Sedentary lifestyles among college students are a public health concern, associated with health risks and a decline in VO₂ max. This study aimed to systematically review the effectiveness of Tabata exercise interventions in addressing this issue among college students. We employed a systematic review of articles published between 2015 and 2025, focusing on studies that measured VO₂ max, body composition, and lipid profile. The review identified 13 eligible studies from a total of 400 records identified in database searches. Key findings indicate that Tabata exercise significantly improved VO₂ max and body composition in sedentary and overweight students. However, its effects on lipid profiles were less consistent and require further exploration. Overall, Tabata exercise is a practical intervention for improving students' cardiovascular health and physical fitness.